The Brood Ball of Canthon (Canthon) Lituratus Germar (Coleoptera: Scarabaeidae: Scarabaeinae) and Its Fossil Counterpart Coprinisphaera cotiae Sánchez and Genise New Ichnospecies, with a Brief Review of South American Fossil Brood Balls - Sánchez, María Victoria (2015)
The brood ball of Canthon (Canthon) lituratus Germar is an elongated ovoid covered by a thin lining of soil and dung fibers. The provision is mostly composed of dung and scattered flakes of organic matter. The egg chamber, which is located in the upper part of the provision, shows no evidence of lining and is connected to the exterior through an elongated aeration conduit. This conduit, which acts as a filter, is filled with interlaced dung fibers. These brood ball features are compared with those reported for several coprophagous species of Canthon Hoffmansegg. The brood ball of C. lituratus is also compared with a similar new fossil brood ball from the Cenozoic of Patagonia: Coprinisphaera cotiae Sánchez and Genise, new ichnospecies. A brief review of South American fossil brood balls in the ichnogenera Coprinisphaera Sauer and Quirogaichnus Laza is also provided with illustrations of the types.